The principle of proportionality under democratic scrutiny: towards a comprehensive method for the analysis of human rights restrictions - Garat, María Paula (Revista de Investigações Constitucionais, 2025)
This paper aims to answer the question of how democracy is and should be considered in the analysis of limitations on fundamental rights. The case law is based on the I/A Court HR and ECtHR decisions, consequently considering the ACHR and the ECHR. In particular, the paper focuses on the interpretation of the "necessary in a democratic society" clause, a requirement stated in both the ECHR and the ACHR. It proposes to add a first step to the analysis of human rights limitations prior to the proportionality test. The paper builds this step on solid theoretical foundations, in attendance of some of the critics of the proportionality exam and based on theories that put coherence in legal systems at the centre. Furthermore, the research aims to demonstrate the need for this stage through the connection between the effectiveness of rights and the consistent and coherent application of the current human rights treaties.